1122. Evaluation of Fecal Microbiota Transplant (FMT) in Elderly Patients With recurrent Clostridium difficile Infection (CDI). (26th November 2018) - Hassoun, Ali; Edwards, Jonathan
Abstract: Background: CDI is a bacterial infection that typically occurs after the use of broad-spectrum antibiotics. Older adults are particularly susceptible to this potentially deadly disease and at higher risk of recurrence. Methods: The study was approved by the hospital's IRB. Patients 65 years of age and older with refractory or recurrent CDI who received FMT administered via colonoscopy or oral capsules were included. Patients with severe-complicated infection were excluded and ineligible to receive FMT. Each patient was evaluated 8 weeks post-transplant to assess for sustained clinical response and adverse events. Data collection included patient demographics, number of recurrent CDI episodes, CDI severity, previous antibiotic treatment regimens, clinical cure, adverse events, and donor information. Results: Thirty-five patients were enrolled (23 colonoscopy FMT vs. 13 oral capsule FMT). One patient received FMT via colonoscopy twice. Mean age was 77 years [65–93], female 60%, median recurrent episode was 3, and median CDI severity score was 2. Total success rate was 69.4% (25/36), 60.9% (14/23) via colonoscopy vs. 84.6% (11/13) via capsule. Total success rate for female 67% vs. 73% male and age group of 65–75 was 60% vs. 76% in age group 75+. For capsules only, cure rate was 80% in female vs. 100% in male and 75% in 65–75 age group vs. 89% in patients older than 75 while in colonoscopy only group, success rate was 55% in female vs. 67% in males and 46% in 65–75 age group vs. 67% in age group 75+. There did not seem to be a correlation between FMT donor and success rate. No serious adverse events were reported in the study population. Conclusion: FMT may be considered a potentially useful therapy for the treatment of refractory or recurrent CDI cases in patients 65 years of age and older. Further studies are needed to confirm the above findings. Older adults are particularly susceptible to this potentially deadly disease Disclosures: All authors: No reported disclosures.